Kathy’s Trauma Response as a Means of Recovery in Kazuo Ishiguro’s Never Let Me Go - Akbar, Muzakki Kamal (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Trauma is a psychological condition resulting from distressing events experienced by an individual, leading to ongoing mental and emotional pain throughout their life. Survivors of trauma often develop various trauma responses, which act as implications or triggers stemming from their traumatic experiences. These mechanisms are essential for individuals to undergo in order to achieve healing and recovery from their trauma. This study aims to analyze how Kathy’s trauma responses influence her journey toward recovery in Kazuo Ishiguro’s novel Never Let Me Go. The novel presents Kathy’s narration about her experiences as a career and how she endures traumatic events, particularly the knowledge of her existence as a clone with a fated life, which generates traumatic responses in various aspects of her life. This study employs Judith Herman’s model of trauma and recovery, which is divided into three phases: establishment of safety, remembrance and mourning, and reconnection with ordinary life. Using this method, the researcher scrutinizes Kathy’s life as a career and her past throughout the novel. This study hypothesizes that Kathy undergoes trauma in her life, generating traumatic responses in many aspects of her life. However, those trauma responses are essential to be undergone as she eventually manages to achieve healing and recovery, offering her a sense of relief despite her unfortunate existence as a clone with predetermined fate